PENGARUH PENGETAHUAN KEWIRAUSAHAAN, KOMPETENSI SOSIAL DAN LINGKUNGAN BISNIS TERHADAP PERTUMBUHAN USAHA (Studi Pada Rumah Makan di Kecamatan Tembalang, Semarang) - Kinanti Hanifati; Ari Pradhanawati (Jurnal Ilmu Administrasi Bisnis, 2017)
The purpose of this research to determine the influence of Entrepreneurship Knowledge, Social Competence and Business Environment to Business Growth at Restaurant in Tembalang District, Semarang. This research type is explanatory research. Sampling technique is using non probability sampling with 90 samples of business owners. Technique of data collection with questioner and documentation. Data analysis technique used validity test, reliability test, correlation coefficient test, simple linear regression test, coeficient of determination (R2), partial significance test (t test) and simultant significance test (f test) using SPSS 16.0 for windows. Based on the results of the analysis, partially and simultantly entrepreneur knowledge, social competence and business environment have an influence on business growth. Suggestions for restaurant business owners in Tembalang District is to increase the knowledge related to business management especially on their human resources so their business can grow better.